2021
DOI: 10.3390/cells10051246
|View full text |Cite
|
Sign up to set email alerts
|

Store Operated Calcium Entry in Cell Migration and Cancer Metastasis

Abstract: Ca2+ signaling is ubiquitous in eukaryotic cells and modulates many cellular events including cell migration. Directional cell migration requires the polarization of both signaling and structural elements. This polarization is reflected in various Ca2+ signaling pathways that impinge on cell movement. In particular, store-operated Ca2+ entry (SOCE) plays important roles in regulating cell movement at both the front and rear of migrating cells. SOCE represents a predominant Ca2+ influx pathway in non-excitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 142 publications
0
32
0
Order By: Relevance
“…We next performed studies for identifying potential mechanisms functioning downstream of Orai3 for regulating PC metastasis. Since metastasis is a very complex phenomenon involving several steps, based on the literature survey suggesting a role for SOCE in regulating MMP expression and EMT [ 42 , 43 , 44 , 45 ], we only focused on MMP expression and EMT in this study. Recently, STIM1-Orai1 mediated SOCE was shown to regulate expression of key metastasis associated MMP2 expression [ 43 ] in cancerous cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next performed studies for identifying potential mechanisms functioning downstream of Orai3 for regulating PC metastasis. Since metastasis is a very complex phenomenon involving several steps, based on the literature survey suggesting a role for SOCE in regulating MMP expression and EMT [ 42 , 43 , 44 , 45 ], we only focused on MMP expression and EMT in this study. Recently, STIM1-Orai1 mediated SOCE was shown to regulate expression of key metastasis associated MMP2 expression [ 43 ] in cancerous cells.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, our in vivo studies suggest that Orai3 regulates PC metastasis ( Figure 9 ). Indeed, the role of Orai channels mediated SOCE in driving cancer cell migration and metastasis is starting to emerge in a variety of cancer types [ 44 , 45 , 50 ]. However, molecular mechanisms driving metastasis downstream of SOCE remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our in vivo studies suggest that Orai3 regulates PC metastasis (Figure 9). Indeed, the role of Orai channels mediated SOCE in driving cancer cell migration and metastasis is starting to emerge in a variety of cancer types [44,45,50]. However, molecular mechanisms driving metastasis downstream of SOCE remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…We next performed studies for identifying potential mechanisms functioning downstream of Orai3 for regulating PC metastasis. Since metastasis is very complex phenomenon involving several steps, based on literature survey suggesting role of SOCE in regulating MMP expression and EMT [42][43][44][45], we only focused on MMP expression and EMT in this study. Recently, STIM1-Orai1 mediated SOCE was shown to regulate expression of key metastasis associated MMP2 expression [43] in cancerous cells.…”
Section: Orai3 Regulates Pc Progression and Metastasis In Vivomentioning
confidence: 99%
“…Among all the actors involved in cell migration, calcium (Ca 2+ ) plays a pivotal role [ 13 ]. Numerous studies have demonstrated the role of Ca 2+ influx in regulating the migration of cancer cells and more specifically breast cancer cells [ 14 , 15 , 16 ]. Orai channels, whose activity is linked to the filling state of intracellular Ca 2+ stores, are among the major players in mediating the entry of Ca 2+ into non-excitable cells [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%